Eksistensi Audit Laporan Dana Kampanye Pada Pemilihan Umum Kepala Daerah di Indonesia - Henry Windrianto Darmoko; Herry Purnomo; Fatchurrahman (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
The phenomenon that occurs in Indonesia indicates that the existence of campaign fund report audits in Indonesia is weak and even doubtful. This study aims to reveal the existence of campaign fund report audits in regional head elections in Indonesia. The truth of the existence of campaign fund report audits in regional head elections will be proven through the disclosure of the existence of the implementation of campaign fund report audits. The concept of existence in this study uses Paul Sartre's Existentialism Philosophy which states that: "Existence precedes essence",. This study is a qualitative study using transcendental phenomenological analysis techniques Moustakas,. The results of the study revealed that KAP auditors are professional auditors who always build a good reputation and have shown real existence when carrying out the work of auditing campaign fund reports in regional head elections by making thorough preparations by maintaining their professional ethics.